Improving Investment Climates : An Evaluation of World Bank Group Assistance - Independent Evaluation Group (Washington, DC : World Bank, 2012)
This evaluation assesses the effectiveness of the World Bank Group in helping its member countries improve their investment climates, within the context of the World Bank Group's overall mission of poverty reduction and sustainable development.